Design, manufacture, and analysis of customized phantoms for enhanced quality control in small animal MRI systems. Issue 2 (25th February 2013) - Yoshimaru, Eriko; Totenhagen, John; Alexander, Gene E.; Trouard, Theodore P.
<x xml:space="preserve">Abstract</x> Purpose Magnetic resonance imaging (MRI) is widely used in human brain research to evaluate the effects of healthy aging and development, as well as neurological disorders. Although standardized methods for quality assurance of human MRI instruments have been established, such approaches have typically not been translated to small animal imaging. We present a method for the generation and analysis of customized phantoms for small animal MRI systems that allows rapid and accurate system stability monitoring. Methods Computer‐aided design software was used to produce a customized phantom using a rapid prototyping printer. Automated registration algorithms were used on three‐dimensional images of the phantom to allow system stability to be easily monitored over time. Results The design of the custom phantom allowed reliable placement relative to the imaging coil. Automated registration showed superior ability to detect gradient changes reflected in the images than with manual measurements. Registering images acquired over time allowed monitoring of gradient drifts of less than one percent. Conclusion A low cost, MRI compatible phantom was successfully designed using computer‐aided design software and a three‐dimensional printer. Registering phantom images acquired over time allows monitoring of gradient stability of the MRI system. Magn Reson Med 71:880–884, 2014. © 2013 Wiley Periodicals, Inc.